PELATIHAN SERTIFIKASI BALAI BESAR POM DAN HALAL BAGI POKLAHSAR RUMAH LELE ATHALLAH SERTA SIVITAS AKADEMIK UNIVERSITAS SUMATERA SELATAN - Guttifera Guttifera; Selly Ratna Sari; Rani Ria Rizki; Egi Yovandre (Universitas Mataram, 2023)
Business Actors (Micro, Small and Medium Enterprises) must pay attention to safety requirements along the supply chain so people are guaranteed health and safety when consuming products. Every Muslim consumer will pay attention to the halalness of a product before consumption, even becoming a mandatory necessity. One of the problems that makes the competitiveness of Micro, Small and Medium Enterprises is still low, the limited ability of business actors to be registered in BPOM and Halal on product packaging. This community service activity aims to improve the Safety Standards of commercial products certified by BPOM and Halal. Training activities were carried out at Campus C of the University of South Sumatra, Jakabaring, Banyuasin, South Sumatra. The results are registration training in managing BPOM distribution permits and training on the requirements to obtain Halal certification on the products of Micro, Small and Medium Enterprises actors. The activities carried out during the training was attended by 50 participants consisting of Lecturers at the University of South Sumatra, members of the pohlaksar rule athallah and students of the University of South Sumatra. The conclusion obtained is that BPOM certification training activities and Halal certification can increase the knowledge of Poklasar Rule Athallah business actors, and knowing about the products produced must not resemble something that haram, both naming and materials used.